Hubungan Gaya Kepemimpinan Transformasional dan Iklim Organisasi terhadap Job Crafting - Stevi Becher Sengkey; Isaac Jogues Kiyok Sito Meiyanto (Faculty of Psychology, Universitas Gadjah Mada, 2016)
This study aims to determine whether the perception of leadership style andorganizational climate are together able to contribute to job crafting on salespeople, aswell as to know the amount of contribution from the two variables to job crafting. Datacollection was conducted on 79 employees of salespeople in PT. A in Manado, byproviding questionnaires containing three (3) scale of research, namely job crafting scale,transfor-mational leadership scale, and organizational climate scale. The findings of thisstudy indicate that together, the variables of work climate and transformationalleadership are able to contribute R value of 0.443 (p <0.05) to job crafting, with thedeterminant coefficient (R2) of 0.196 or 19.6%. Thus, it can be concluded that the existenceof transformational leadership style and work climate that is considered positive andsupportive can increase the proactive efforts of employees in making changes to balancejob demands and job resources.